Efektivitas Citicoline dalam Terapi Demensia - Ar Rochmah, Mawaddah; Indrihapsari, Erupsiana Fitri; Nugroho, Dhite Bayu (PT Kalbe Farma Tbk., 2024)
Background: In the development of pharmacological therapy for dementia, especially Alzheimer's disease, several types of therapy are widely used: acethylcholine esterase inhibitors/AChEI, N-methyl-D-aspartate (NMDA) receptors inhibitors, and cholinergic precursor. Aim: To review the evidence on the effectiveness of citicoline supplementation to the standard therapy of dementia to prevent the progression or improve the manifestations of dementia. Methods: A literature search was performed in three following databases: Pubmed, EBSCOhost, Scopus, and Cochrane within the last ten years. Results: Of the 239 articles, five studies were eligible for critical appraisal. Four studies showed a significant mean MMSE score increase in the citicoline + standard therapy group (intervention) compared to the standard therapy group (control) during the follow up period between 3 – 12 months. One study showed a significant mean MMSE score increase of in the intervention group compared to the control group. Conclusion: Oral citicoline supplementation of 1,000 mg/day to the standard therapy showed a positive effect on cognitive function in dementia patients. Critical appraisal of validity and application of the included studies should be considered upon daily clinical application.